Higher order spectral analysis of ventricular arrhythmic ECG Signals with MATLAB HOSA toolbox - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
In signal processing methods using second order statistics and / or power spectrum, phase relationships between frequency components are not considered. For this reason these methods are blind to the phase. Second order statistics and power spectrum are also not sufficient to statistically define the non-gaussian processes. In recent years, random processes have been defined as more statistically more sensitive, and high-order statistics (greater than two) and spectrum studies have been carried out to process phase information. In this study, high-order spectral analyzes were performed on ECG recordings in MIT-BIH Malignant Ventricular Arrhythmia and MIT-BIH Normal Sinus Rhythm databases. The obtained results were compared and tried to determine signal abnormalities with the help of higher order spectral analysis methods (Bispectrum, Wigner-Ville Distribution etc.). Analyzes were performed using the MATLAB HOSA toolbox. © 2018 IEEE.
Keywords: ECG; Higher Order Spectral Analysis; MATLAB HOSA Toolbox; Ventricular Arrhythmia